Play, reflect, cultivate social and emotional learning: a pathway to pre-service teacher SEL through playful pedagogies - Darwich, Lina; DeBay, Dennis; Forbes, Lisa; Mahfouz, Julia (Frontiers in Education, 2025)
Playful pedagogies, rooted in experiential learning, integrate play, humor, spontaneity, and levity to create engaging educational experiences. Playful pedagogies have been shown to support adults' emotional resilience and sense of belonging while reducing stress and anxiety. Despite these benefits, their use in education preparation programs (EPPs) remains underexplored. Given the increasing focus on teacher social and emotional learning (SEL), playful pedagogies hold significant potential for equipping future educators with the skills needed to foster both their own and their students' SEL growth. This paper advocates for a shift in teacher education from predominantly lecture-based instruction to a model that incorporates joy, humor, and experiential learning. We propose integrating playful pedagogies with a reflective learning cycle to enhance SEL competencies among pre-service teachers. Specifically, we introduce a conceptual model that combines a four-level pyramid of playful learning with an iterative reflection process. By integrating playful pedagogy into EPPs, we aim to foster resilience, creativity, and collaboration among future teachers, empowering them to create inclusive learning environments that nurture their students' holistic development.